A Meta-Analysis Evaluating the Incidence of Bleeding Events With Intravenous Defibrotide Treatment Outside the Veno-Occlusive Disease/Sinusoidal Obstruction Syndrome Setting. (18th September 2020) - Tappe, William; Aggarwal, Saurabh; Topaloglu, Ozlem; Iacobelli, Massimo
Defibrotide is approved to treat hepatic veno-occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) with renal/pulmonary dysfunction following hematopoietic cell transplantation (HCT) in adult and pediatric patients in the United States, and to treat severe hepatic VOD/SOS post-HCT in adult and pediatric patients aged >1 month in the European Union. The defibrotide prescribing information warns that defibrotide may increase bleeding risk in VOD/SOS patients. To broaden our understanding of the incidence of bleeding with defibrotide, we performed a meta-analysis of the published literature of defibrotide use outside of the post-HCT VOD/SOS setting. Of 1857 records identified, 125 reported on defibrotide; 23 contained data on bleeding events. The estimated overall incidence of bleeding events was 1% (95% confidence interval [CI]: 0%-2%) and 8% (95% CI: 3%-14%) in studies using intravenous defibrotide and studies with controls, respectively. The risk ratio for bleeding events with intravenous defibrotide versus controls was 0.36 (95% CI: 0.24-0.52; P < .00001) among studies with data on intravenous defibrotide and controls. This meta-analysis of defibrotide use outside of the post-HCT VOD/SOS setting suggests that the incidence of bleeding with defibrotide is lower than controls.